A three-dimensional model comparison of PSC processing during the Arctic winters of 1991/1992 and 1992/1993 - M. P. Chipperfield
A three-dimensional transport model has been used to compare and contrast the extent of processing by polar stratospheric clouds during the northern hemisphere winters of 1991/1992 and 1992/1993. The model has also been used to compare the potential for ozone loss between these two winters. The TOMCAT off-line model is forced using meteorological analyses from the ECMWF. During winter 1992/1993 polar stratospheric clouds (PSCs) in the model persisted into late February/early March, which is much later than in 1991/1992. This persistence of PSCs should have resulted in much more ozone loss in the later winter. Interestingly, however, the extent of PSC processing and ozone loss was greater in January 1992 than January 1993. In January 1992 PSCs occurred at the edge of a distorted polar vortex whilst in January 1993 the PSCs were located at the centre of a much more zonally symmetrical vortex. In March 1993, distortions of the vortex led to the tearing off of vortex air and its mixing into midlatitudes.